Effect of Tai Chi Chuan in Breast Cancer Patients: A Systematic Review and Meta-Analysis - Luo, Xiao-Chao; Liu, Jie; Fu, Jia; Yin, Hai-Yan; Shen, Li; Liu, Mai-Lan; Lan, Lei; Ying, Jian; Qiao, Xiu-Lan; Tang, Chun-Zhi; Tang, Yong (Frontiers in Oncology, 2020)
Background: Tai Chi Chuan(TCC), as a mind-body exercise, may have a positive impact on physical function and psychological well-being in breast cancer patients. The latest systematic review and meta-analysis of TCC for breast cancer was made 4 years ago and some new clinical trials about it were published. We remade a systematic review and meta-analysis to evaluate the effect of TCC in breast cancer patients. Methods: In this systematic review and meta-analysis, we searched MEDLINE (via PubMed), EMBASE (via embase.com), CENTRAL, CNKI, COVIP, Wanfang, Chaoxing, CiNii, J-SSTAGE, DBpia, and ThaiJO with no language restrictions from inception to December 31, 2018 (updated on February 16, 2020), for randomized clinical trials comparing TCC with non-exercised therapy in breast cancer patients. The primary outcome was quality of life in patients with breast cancer and data pooled by a random-effects model. Subgroup analyses were conducted to estimate the effect of different durations of TCC for breast cancer patients. This study was registered in PROSPERO, number CRD 4201810326. Results: Fifteen articles involving a total of 885 breast cancer participants were included in this review. Compared with non-exercised therapy, TCC had a significant effect on quality of life in breast cancer patients (SMD = 0.37, 95% CI 0.15–0.59, p = 0.001), and subgroup analysis found that TCC showed beneficial effect in 12 weeks and 25 weeks (12 weeks: SMD = 0.40, 95% CI 0.19–0.62, p = 0.0003; 25 weeks: SMD = 0.38, 95% CI 0.15–0.62, p = 0.002). Meta-analyses of secondary outcomes showed that 3 weeks TCC increased shoulder function (SMD = 1.08, 95% CI 0.28–1.87, p = 0.008), 12 weeks TCC improved pain (SMD = 0.30, 95% CI 0.08–0.51, p = 0.007), shoulder function (SMD = 1.34, 95% CI 0.43–2.25, p = 0.004), strength of arm (SMD = 0.44, 95% CI 0.20–0.68, p = 0.0004), and anxiety (MD = −4.90, 95% CI −7.83 to −1.98, p = 0.001) in breast cancer patients compared with the control group. Conclusions: TCC appears to be effective on some physical and psychological symptoms and improves the quality of life in patients with breast cancer. Additional randomized controlled trials with a rigorous methodology and low risk of bias are needed to provide more reliable evidence.